Vasculature of skin and associated structures in camel - GOSWAMI, S K; DHINGRA, L D; NAGPAL, S K (The Indian Journal of Animal Sciences, 2013)
Tissues from 34 body areas were studied for regional distribution of blood supply in skin of camel. The dermis was richly supplied bv blood vessels particularly on the dorsal body areas. Four levels of blood plexuses were seen, viz. first in deep reticular level, second at mid-reticular level. third in between sweat gland and sebaceous gland level, and fourth in sub-epidermal area. In addition to this arteriovenous anastomoses, individual epithelioid arterioles and intra-artcrial cushions were also encountered In dernis.